Re-contando a história da Escola Técnica Federal do Pará: a educação profissional em marcha de 1967 a 1979. - Lobato, Ana Maria Leite (2012)
This study aimed to investigate the (re) configuration of Professional Education in high school in ETFPA from educational policies, implemented in reconstructing history from 1967 to 1979. It was a concentrated work in History Education, which sought to anchor in Cultural History (size) in History of Time Oral History and the Present (approach) through the narratives of some actors who made this school a memory space. The findings were supplemented by documentary information such as the Internal ETFPA, the Report of the Fourth Meeting of Directors of the Federal Technical Schools (IV Revenue), laws and decrees concerning the professional education of the federal network in Brazil. Presents an investigation with the following path: a) the historical Vocational Education under the auspices of the federal system of education in Brazil through educational policies (1909-1970), b) the professionalization at technical courses, considering the educational policies and the relationship school-company during the period 1967 to 1979, c) educational practices considering the proposal of professionalization of Professional Education ETFPA in the period 1967 to 1979. The method used was qualitative, descriptive narrative through the interview, the dialectical hermeneutic circle, and documentary research, prevailing narratives. During field research we conducted interviews with some teachers, students and director of ETFPA the time. The results show consensus on the ways of realization of professionalism in the relationship business school, the educational practices of discipline directed to the labor market, also have some differing views about the professional practices through education at school. Finally, the study presents findings mainly through orality, which gives consistency needed to (re) composition of the history of the Federal Technical School of Para, was showing how to (re) organization of professional education at the institution.